Preliminary Considerations of Options to Address Excessive Delays in the Completion of Article IV Consultations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper aims to engage Directors on how best to promote timely completion of Article IV consultations. Surveillance is mandatory for both the Fund and its members, and members have an obligation to consult with the Fund for this purpose. In this context, it is useful to consider if further steps are warranted to address cases in which members do not consult with the Fund on a timely basis. This paper does not propose Board decisions at this stage. Instead it lays out ideas to elicit Directors' views. Based on this informal discussion, staff could return later to the Board, if needed for a formal discussion and possible decisions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet